Quantifying the Evolutionary Conservation of Genes Encoding Multidrug Efflux Pumps in the ESKAPE Pathogens To Identify Antimicrobial Drug Targets - Lauren E. Brooks (American Society for Microbiology, 2018)
ABSTRACT Increasing rates of antibiotic-resistant bacterial infection are one of the most pressing contemporary global health concerns. The ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) have been identified as the leading global cause of multidrug-resistant bacterial infections, and overexpression of multidrug efflux (MEX) transport systems has been identified as one of the most critical mechanisms facilitating the evolution of multidrug resistance in ESKAPE pathogens. Despite efforts to develop efflux pump inhibitors to combat antibiotic resistance, the need persists to identify additional targets for future investigations. We evaluated evolutionary pressures on 110 MEX-encoding genes from all annotated ESKAPE organism genomes. We identify several MEX genes under stabilizing selection—representing targets which can facilitate broad-spectrum treatments with evolutionary constraints limiting the potential emergence of escape mutants. We also examine MEX systems being evaluated as drug targets, demonstrating that divergent selection may underlie some of the problems encountered in the development of effective treatments—specifically in relation to the NorA system in S. aureus. This study provides a comprehensive evolutionary context to efflux in the ESKAPE pathogens, which will provide critical context to the evaluation of efflux systems as antibiotic targets. IMPORTANCE Increasing rates of antibiotic-resistant bacterial infection are one of the most pressing contemporary global health concerns. The ESKAPE pathogen group represents the leading cause of these infections, and upregulation of efflux pump expression is a significant mechanism of resistance in these pathogens. This has resulted in substantial interest in the development of efflux pump inhibitors to combat antibiotic-resistant infections; however, no widespread treatments have been developed to date. Our study evaluates an often-underappreciated aspect of resistance—the impact of evolutionary selection. We evaluate selection on all annotated efflux genes in all sequenced ESKAPE pathogens, providing critical context for and insight into current and future development of efflux-targeting treatments for resistant bacterial infections.